Specific antibody and immunoglobulin responses after intestinal colonization of germ-free piglets with non-pathogenic Escherichia coli O86 - Cukrowska, B; Kozáková, H; Reháková, Z; Sinkora, J; Tlaskalová-Hogenová, H (Immunobiology, 2001)
Colonization of the gut with components of commensal microflora profoundly affects the development of the immune system. The aim of the present study was to investigate mucosal and systemic B cell responses during the first few days after intestinal association of colostrum-deprived piglets reared in germ-free (GF) conditions with non-pathogenic Escherichia coli O86. Specific intestinal anti-E. coli antibodies (Ab), among which IgA Ab prevailed, were found 4 days after colonization (72% of standard) and their amount decreased 11 days later reaching 22% of standard. In contrast to mucosal Ab, specific serum Ab remained at the level of GF animals at day 4 (less than 10% of standard) and markedly increased 15 days after colonization (156% of standard). In addition to the occurrence of specific Ab, increased amounts of total immunoglobulins (Ig) of all isotypes were detected in sera and intestinal washings. Using the ELISPOT method an increased number of IgM, IgG and IgA-secreting lymphocytes were found in spleen, mesenteric lymph nodes (MLN) and Peyer's patches (PP) in colonized animals as compared to GF piglets. Contrary to cells from these lymphatic organs, B cells from thymus were not affected by E. coli stimulation. Our results show that at the onset of intestinal colonization, non-pathogenic E. coli specifically and polyclonally stimulate the mucosal and systemic humoral immunity, but relatively soon after stimulation, mucosal-specific responses in gut decreases, indicating the possible beginning of inhibition mechanisms (oral tolerance).
Keywords: infekce vyvolané Escherichia coli; Escherichia coli Infections; Immunoglobulins; střeva; Intestines; střevní sliznice; protilátky bakteriální; ELISA; Escherichia coli; zvířata; Enzyme-Linked Immunosorbent Assay; Swine; Antibodies, Bacterial; Animals; Disease Models, Animal; Intestinal Mucosa; imunoglobuliny; prasata; modely nemocí na zvířatech